Icnofósseis em afloramentos do Rio Grande do Sul: nota preliminar - Dutra, Tânia L.; Netto, Renata G.; Nowatzki, Carlos H.; Figueiredo, Cláudio E. Zarif (Ciência e Natura, 1990)
O trabalho não apresenta resumo.